Waste fibre reinforced ecocomposites - Lundahl, A. (2010)
With a significant production of waste fibrous material, textile companies are now looking for applications where waste materials could be an added-value material. One viable application of these waste materials is in the combination with polymeric matrices, producing composite materials with interesting properties for specific applications, from furniture to thermal and acoustic insulations. The aim of this work was to study the physical and mechanical properties of waste fibre reinforced composites and the influence of different parameters on their mechanical behaviour. Results show that a wide range of different properties and performances may be designed by altering various production parameters, such as thickness of the nonwovens used, time and temperature of the compression moulding, relationship between fibre/matrix ratio, polymeric film used and number of layers.